2020
DOI: 10.1016/j.scitotenv.2020.140101
|View full text |Cite
|
Sign up to set email alerts
|

The effects of regional climatic condition on the spread of COVID-19 at global scale

Abstract: The study explores the effect of regional climatic conditions on the spread of COVID-19. • The regional climate parameters are important factors that may trigger the spread of the COVID-19. • The fast-spreading of COVID-19 has an association with average high and low temperatures. • The average daylight hours have a connotation with the spreading rate of pandemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 85 publications
(164 reference statements)
7
92
1
6
Order By: Relevance
“…An uncontrolled outbreak of COVID-19, e.g., 11 , starts with an exponential growth, the rate of which is presumably modulated by external factors such as weather [4][5][6] . We estimate the growth rate through a sliding window regression for each country and investigate its response to meteorological conditions across all countries, in contrast to the above-mentioned works [7][8][9][10] , which analyzed the number of confirmed cases or mortality from prior selected cities directly. Therefore, our results allow capturing straightforward the modulation of the weather and are not subject to potential statistical bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An uncontrolled outbreak of COVID-19, e.g., 11 , starts with an exponential growth, the rate of which is presumably modulated by external factors such as weather [4][5][6] . We estimate the growth rate through a sliding window regression for each country and investigate its response to meteorological conditions across all countries, in contrast to the above-mentioned works [7][8][9][10] , which analyzed the number of confirmed cases or mortality from prior selected cities directly. Therefore, our results allow capturing straightforward the modulation of the weather and are not subject to potential statistical bias.…”
Section: Resultsmentioning
confidence: 99%
“…Their conclusions, however, are controversial. Some attempts did not find the correlation, e.g., 6,7 , whereas the others reported weak or moderate correlations, e.g., [8][9][10] . The results are not conclusive, mainly because the meteorological modulations are constrained by non-meteorological effects.…”
Section: Introductionmentioning
confidence: 98%
“…Pakistan's climatic condition is moderate, as it included both high and low temperature that can be seen in different parts of a country. The number of earlier studies largely provoked that regional climatic conditions would be helpful to access the intensity of coronavirus cases, for instance, Iqbal et al (2020) found that COVID-19 cases are largely exacerbated in the relatively lower temperature region compared with the other countries located in the warmer climatic zone. Bukhari and Jameel (2020) argued that although few evidences related with diminishing COVID-19 cases supported in high climatic temperature zone, it is a need to use effective public healthcare interventions to reduce new cases.…”
Section: Covid-19 and Pakistan's Climatic Conditionmentioning
confidence: 99%
“…In addition, with increasing temperature, the prevalence of the disease has decreased 8 . The average temperature and daylight hours have shown a positive association towards the spread rate of COVID-19 1 . The growth rate of COVID-19 cases peaked at a temperature of ~5°C and a humidity of 0.6 to 1 kPa in the temperate regions of the Northern Hemisphere during the outbreak month, while it decreased in regions that had warmer or colder temperatures 9 .…”
mentioning
confidence: 94%
“…The pandemic diseases have been some of the most distressing happenings in the history of mankind 1 . At present, the world is facing the Covid-19 pandemic.…”
mentioning
confidence: 99%